Purulent Pericarditis in Sickle Cell Disease Due to Streptococcus agalactiae; a Unique Case Report and Literature Review. (2nd January 2019) - Bhat, Alina; Neculiseanu, Elvira; Tam, Eric L.; Gendy, Adam; Beckles, Daniel L.; Luhrs, Carol; Braverman, Albert
Abstract: Purulent pericarditis is a localized infection with a thick, fibrinous hypercellular exudate and is historically associated with a high mortality. We describe a case of purulent pericarditis due to Streptococcus agalactiae (S. agalactiae) in a 30-year-old woman with sickle cell disease who presented with fever, dyspnea, and S. agalactiae septicemia. Despite timely initiation of antibiotics, she developed a large purulent pericardial effusion requiring surgical pericardiocentesis followed by a pericardial window. At 14 months follow-up, she has remained asymptomatic without sequelae. A review of the literature contained only four patients with purulent pericarditis in sickle cell patients. We discuss the unique aspects of this case in the context of purulent pericarditis in the age of modern antibiotics and hypothesize on the pathogenesis of delayed pericardial effusion after pericarditis.